Structure-guided selection of puromycin N-acetyltransferase mutants with enhanced selection stringency for deriving mammalian cell lines expressing recombinant proteins - Alessandro T. Caputo (Nature Portfolio, 2021)
Abstract Puromycin and the Streptomyces alboniger-derived puromycin N-acetyltransferase (PAC) enzyme form a commonly used system for selecting stably transfected cultured cells. The crystal structure of PAC has been solved using X-ray crystallography, revealing it to be a member of the GCN5-related N-acetyltransferase (GNAT) family of acetyltransferases. Based on structures in complex with acetyl-CoA or the reaction products CoA and acetylated puromycin, four classes of mutations in and around the catalytic site were designed and tested for activity. Single-residue mutations were identified that displayed a range of enzymatic activities, from complete ablation to enhanced activity relative to wild-type (WT) PAC. Cell pools of stably transfected HEK293 cells derived using two PAC mutants with attenuated activity, Y30F and A142D, were found to secrete up to three-fold higher levels of a soluble, recombinant target protein than corresponding pools derived with the WT enzyme. A third mutant, Y171F, appeared to stabilise the intracellular turnover of PAC, resulting in an apparent loss of selection stringency. Our results indicate that the structure-guided manipulation of PAC function can be utilised to enhance selection stringency for the derivation of mammalian cell lines secreting elevated levels of recombinant proteins.